Nilai-Nilai Pendidikan dalam Shalat Fardhu Perspektif Ulama Fikih Klasik dan Kontempor - Sulfani Sulfani; Silvia Purwitasari; Fathiyah Naura Al-ansori; Andriyani Andriyani; Irna Hasanah (Jurnal Budi Pekerti Agama Islam, 2026)
Obligatory prayer is a fundamental act of worship in Islam; performing it earns reward, while neglecting it results in sin for those who have fulfilled the required conditions, namely being of legal age (baligh), of sound mind, and free from ritual impurity (hadath). The background of this study is important for understanding how the values upheld by classical fiqh scholars and Islamic teachings can be interpreted in a way that connects traditional understanding with the needs of the Muslim community in the modern era. This research aims to identify, analyze, and compare the values of farḍu prayer based on the perspectives of different groups of scholars. The results show that classical scholars emphasize values such as obedience, order, legal aspects, discipline, and devotion (khushu’). In contrast, contemporary scholars place greater emphasis on personal transformation, social ethics, and the importance of prayer in shaping the character of the modern Muslim.The conclusion is that these two perspectives can be integrated to provide a more comprehensive understanding of the values of farḍu prayer that remain relevant for all times. Farḍu prayer holds a central position in Islam as the second pillar of Islam after the declaration of faith (shahada) and consists of five daily prayers: Fajr, Dhuhr, Asr, Maghrib, and Isha.